Remediation of Heavy Metals form Wastewater by Nanomaterials - Ojha A.; Tiwary D. (My University, 2025)
Nanomaterials have been well exploited and used for their application in environmental remediation. The role of nanomaterials swings from application in the detection of pollutants, their remediation to find a suitable substitute for the contaminants. The nanomaterials have been used for the treatment of wastewater, and there are many researchers who have defined their wide range of applications such as filters, membranes, pollutant degradation and adsorption. A variety of pollutants include physical (sediments, particulate matters), chemical (organic and inorganic), biological (microbes and pathogens) and radiological. Inorganic pollutants of wastewater primarily include heavy metal ions and anions, which are harmful to humans and may cause deadly diseases. Nanomaterials have been used extensively for the remediation of metal ions in wastewater. Silica and zeolites, which have been drawn to nanostructures, are excellent when it comes to effectiveness in the treatment of metal ions removal. Their adsorbents, as well as chelating behaviour through surface modifications, are well studied. The chapter covers various aspects of the application of nanomaterials in the field of metal ion removal, and some of these nanomaterials have been discussed here. The limitations of these nanomaterials and their plausible solutions have also been analysed in detail here. © The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Switzerland AG 2022.